Navigating dust storms and urban living: an analysis of particulate matter infiltration in Dubai’s residences - Jung, Chuloh; Abdelaziz Mahmoud, Naglaa Sami (Frontiers in Built Environment, 2023)
Air pollution is a significant concern in Dubai, with this study focusing on measuring and analyzing indoor and outdoor particulate matter (PM) concentrations in residential buildings during the spring dust storm period. By examining the infiltration of PM into indoor spaces and its impact on indoor air quality, the study sheds light on the relationship between PM particle diameter, building infiltration rates, and the indoor influence of outdoor PM. Measurements were conducted in a two-bedroom residential unit near a busy road using particle size analysis and the indoor-outdoor (I/O) ratio. The results indicate that smaller particles, particularly ultrafine PM2.5, influence indoor PM concentrations more strongly than larger particles. Buildings with higher infiltration rates, such as those relying on natural ventilation, are more susceptible to outdoor PM infiltration. The study also highlights the role of occupant behavior, including activities like cooking and cleaning, in indoor PM generation. Further research is needed to understand better the correlation between architectural characteristics, infiltration rates, and the indoor influence of outdoor PM in residential buildings. The study emphasizes the importance of improved ventilation systems, increased awareness of indoor air quality, and effective mitigation strategies to reduce indoor air pollution and improve indoor air quality in urban environments like Dubai. These findings contribute to our understanding of indoor and outdoor PM dynamics and underscore the need to address indoor air pollution in cities.